AN ANALYTICAL STUDY ON THE RELATIONSHIP BETWEEN NUTRITIONAL LITERACY AND ADHERENCE TO DIETARY PROTOCOLS AMONG INDIVIDUALS WITH DIABETES IN ENUGU STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
This paper explores the repercussion between nutritional literacy and adherence to dietary measures set among people with diabetes in Enugu State in Nigeria. The level of nutritional literacy, which includes the capacity to access, understand, and use any information related to nutrition, is essential to manage diabetes properly. The topic of the research fills the knowledge gap regarding the role of nutritional literacy as a variable affecting dietary adherence in a resource-limited environment with distinct socio-cultural interplay. The sample surveyed consisted of 400 individuals with diabetes diagnosis, chosen by means of the purposive sampling of healthcare facilities in Enugu State. Validated questionnaires that were used to determine nutritional literacy and dietary adherence were used to collect the data and supplemented with discussions in focus groups. The results indicate a strong positive relationship exists between nutritional literacy and compliance to dietary guidelines, and the socio-demographic variables: education, income, and access to healthcare services are mediating ones. The research indicates that a specific nutrition education intervention is important to close the literacy gap and achieve better outcomes of diabetes in Nigeria. The measures that come into recommendation involve incorporation of nutritional literacy into primary care, and the ability to use the community platform to promote dietary compliance.